Peripheral CGRP release as a marker for neurogenic inflammation: a model system for the study of neuropeptide secretion in rat paw skin - Kilo, Sonja; Harding-Rose, Catherine; Hargreaves, Kenneth M; Flores, Christopher M (Pain (Amsterdam), 1997)
The local release of pro-inflammatory neuropeptides in the periphery has been associated with the development of neurogenic inflammation. However, there is an increasing number of reports demonstrating tissue-dependent differences regarding the mechanisms engaged by these neuropeptides to initiate and maintain the inflammatory response in the target tissue. Since skin is often involved in tissue injury, the present studies were designed to develop a model for assessing cutaneous peptide secretion as a marker for neurogenic inflammation in skin tissue. Calcitonin gene-related peptide (CGRP), as one of several neuropeptides known to be involved in neurogenic inflammation, was chosen to study capsaicin-induced effects on peripheral neurosecretion. The corial surface of the hairy skin of a rat hindlimb was superfused in vitro, and the basal and capsaicin-evoked peripheral release of immunoreactive CGRP (iCGRP) was measured using a radioimmunoassay. The main objectives of these studies were to characterize the various properties of this release including dose-dependency, exocytosis and receptor-mediation as well as the effects of acute and long-term capsaicin desensitization. Capsaicin significantly and dose-dependently increased the release of iCGRP at concentrations ranging from 3 to 300 microM. Omission of calcium ions or treatment with the competitive capsaicin receptor antagonist capsazepine completely inhibited the capsaicin-induced iCGRP release. Superfusion of the skin with 100 microM capsaicin following a conditioning stimulation with capsaicin at concentrations ranging from 0.3 to 100 microM led to an acute, dose-dependent desensitization of the CGRP response. In addition, chronic desensitization following the neonatal injection of capsaicin completely abolished the acute iCGRP response to capsaicin. The method described here should prove to be a valuable tool for the evaluation of the processes regulating the peripheral, cutaneous release of pro-inflammatory neuropeptides. This strategy, therefore, may lead to a better understanding of the mechanisms involved in the development and maintenance of neurogenic inflammation, particularly in the skin.